KINERJA SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG KAKI LIMA (PKL) DI TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Gusti Pratama Putra; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This Research focused on The performance Satuan Polisi Pamong Praja in Tembilahan for handling result in curbing Street Vendors have not been effective, Limited employee Satuan Polisi Pamong Praja, lack of response to the needs of Street Vendors, and low assertiveness, no tough sanctions in enforcing penalties or sanctions.Method using by researchers is theory of Dwiyanto with the using of indicators are Productivity, Quality of Service, Responsiveness, Responsibility, and Accountability. Method used is qualitative. In collecting The data, the researcher used Interview techniques, Conservation, and Study of literatur. By using Key informan as sources of information. For the location of the research, researchers specializing in Tembilahan.The result showed that the performance of Satuan Polisi Pamong Praja not running optimally, Satuan Polisi Pamong Praja barrier is the lack of employee Satuan Polisi Pamong Praja, Limited budget and no special land for Street Vendors. The works done is conduct roving patrols, outreach to the Street Vendors. Recommendation from this research should Satuan Polisi Pamong Praja Reseachers are more assertive in controlling the Street Vendors.Keywords: Performance, Street Vendors, Control.